Cost-Effective Paramagnetic Bead Technique for Purification of Cycle Sequencing Products. (23rd September 2012) - Mijatovic-Rustempasic, Slavica; Frace, Michael A.; Bowen, Michael D.
Abstract : The quality of sequencing results depends greatly upon the quality and purity of the template as well as the purity of the fluorescently labeled products generated by cycle sequencing. Numerous approaches have been used for purification of cycle sequencing products, including alcohol precipitation, affinity-based chromatography, size exclusion chromatography, commercially-available proprietary methods, and paramagnetic bead technology. In this paper, we describe an affordable paramagnetic technology method using BioMag Carboxyl beads. Compared to other well-established, proprietary methods for purification of cycle sequencing products, this method produced consistently good results, with a very low reagent cost and short procedure time.